Using Cooperative Learning to Foster the Development of Adolescents’ English Writing Skills - Paula Andrea Caicedo Triviño (Profile: Issues in Teachers' Professional Development)
Seventh grade teachers at a Colombian public school chose cooperative learning as a strategy to improve student’s social performance and as a tool to get learners to enrich their academic level. This article reports on an action research and innovation project focused on the results eight students obtained in their written performance in English classes during three cooperative lessons. This article gathers some existing research on writing skills and cooperative learning and a presentation and analysis about students’ real expectations and thoughts about writing in the English language. The systematization of this teaching experience also sheds lights on further actions to analyze closely students’ texts construction in a cooperative environment.